PEMETAAN KOMPETENSI PEDAGOGIK GURU DALAM KETERAMPILAN TEKNOLOGI INFORMASI DAN KOMPUTER - Nani Rohmani (Tatar Pasundan: Jurnal Diklat Keagamaan, 2021)
This study aims to mapping teachers’ pedagogical competence in terms of utilizing Information Technology and Computer (ICT) skills in learning. The research method uses qualitative approach based on the data taken from the Central Bureau of Statistics (BPS). The data sources used are based on the highest proportion of ICT skills which is Yogyakarta at 95.19, and the lowest one is Papua at 32.88. The results concluded that the proportion of ICT skills seen from gender is the same. In economy, the highest proportion is shown by the richest compared to the poorest spending group.  Teachers are required to quickly update their knowledge, skills, and competencies in the field of ICT. However, the uneven development of ICT results digital gap, since Indonesia is a large island nation and has tough challenges to hone the skill. Thus, researchers advise that it is necessary to develop internet network infrastructure throughout Indonesia.Keywords:  Proportion; ICT skills; Mapping; Teacher Competence